DTC710 : Integrated modelling prototype / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
An introductory course that demonstrates the integration of Computer-Aided-Design (CAD) and Computer-Aided-Manufacturing (CAM). The course commences with a brief revision in the use and application of 3D software in the design profession. This is a study of modern prototyping and machining methods, teaching the use of specific software for converting 2D and 3D CAD drawing geometry directly